AN APPROACH FOR SELECTING GREEN ENERGY SYSTEMS FOR NEW GENERATION NAVAL VESSELS - Cui, Selcuk; Celebi, Ugur Bugra (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
Ship-borne air emissions have a significant impact on air pollution as well as global warming, especially in coastal areas. CO2 is the major component of the greenhouse gases (GHGs). Naval vessels constitute a notable part of the total fleet of sea going ships and the fuel burnt in the energy systems of naval vessels is strongly proportional to CO2 emissions. Existing fossil fuel reserves are apparently decreasing, so interrelated fuel efficiency and emissions should be handled together. The increasing need for ensuring safety at sea and protecting sea resources, results in an increase in the need to build new vessels that will provide these missions. Offshore patrol vessels (OPVs) are reasonable solutions to perform these missions compared to naval vessels such as frigates and corvettes, in terms of high investment and life cycle costs. Main air emission source of an OPV is energy system which consists of prime movers and auxiliary engines. This system should comply with mission profile assigned to OPV, providing high fuel efficiency and low air emission. This study analyzes fuel efficiency and proposes an approach for estimation of CO2 emissions of four alternative energy systems for a new generation OPV at the conceptual design phase.
Keywords: CO2; GHGs; emission; fuel efficiency; energy system; naval vessel; EMISSION ESTIMATION; SHIPPING EMISSIONS; GAS EMISSIONS; SHIPS; INVENTORY; FOOTPRINT; REGION; PORTS; POWER; Environmental Sciences & Ecology